PENGEMBANGAN EKONOMI KREATIF DI PONDOK PESANTREN SYEH HASAN YAMANI MELALUI UNIT KEWIRAUSAHAAN PADA ERA DIGITAL - Gufran Darma Dirawan (Universitas Khairun, 2023)
This study aims to describe the development of the creative economy at the Syeh Hasan Yamani Islamic boarding school (SHY) through an entrepreneurship program in the digital era 5.0. The research data analysis method uses descriptive qualitative analysis, to get an overview of the various activities and programs that have been carried out or carried out by the Islamic Boarding School (pesantren) to develop students' knowledge, attitudes and insights towards the digitalization era. Based on the facts and data analyzed by the researchers, an initial synthesis was produced in the digitalization era, the goal is to achieve graduates who have the ability to be able to use and empower students and graduates to be able to increase students' understanding of doing digital marketing so that Islamic boarding schools are not only religious-based educational institutions but able to develop the abilities of students and graduates to be able to increase students' knowledge and insights in an effort to develop for and encourage the local economy, but it cannot be denied that this ability has not been able to encourage the sustainability of Islamic boarding schools' jobs and income, given the limited network capabilities so that it can be concluded that efforts are needed comprehensively so as to be able to develop the business to a more sustainable level. These efforts can be carried out through: (1) First, developing the pesantren curriculum, guidelines for teaching and learning activities in Islamic boarding schools, focusing on the development of human resources (students) through the provision of training, and entrepreneurship education. (2) Second, improving the network and infrastructure of pesantren and the ability of pesantren to prepare teaching staff who have competence in their fields of expertise and experience, so that with the knowledge and skills possessed by teachers, they can encourage enthusiasm and provide direction to the students, (3) Third ̧ strategy or a learning model that focuses on the competency skills of students.